2018
DOI: 10.5152/dir.2018.17378
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the ADNEX MR scoring system based on a simplified MRI protocol for the assessment of adnexal masses

Abstract: PURPOSEWe aimed to evaluate the ADNEX MR scoring system for the prediction of adnexal mass malignancy, using a simplified magnetic resonance imaging (MRI) protocol. METHODSIn this prospective study, 200 patients with 237 adnexal masses underwent MRI between February 2014 and February 2016 and were followed until February 2017. Two radiologists calculated ADNEX MR scores using an MRI protocol with a simplified dynamic study, not a high temporal resolution study, as originally proposed. Sensitivity, specificity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 20 publications
5
26
0
4
Order By: Relevance
“…In 2013, a standardized reporting system for ovarian mass characterization on MRI was proposed [42]. The validity of this five-category ADNEX MR SCORING system was subsequently verified by independent study groups also confirming that it might lead to the standardization of MRI reporting for ovarian masses [43][44][45]. Very recently, the MRI working group for the Ovarian-Adnexal Imaging-Reporting and Data System (O-RADS) confirmed with a prospective multicenter study the performance of the ADNEX MR SCORING system (now called the O-RADS MRI score), that represents the current standard in the field [46].…”
Section: Gynecological Malignancies: Ovarian Masses and Endometrial Cmentioning
confidence: 96%
“…In 2013, a standardized reporting system for ovarian mass characterization on MRI was proposed [42]. The validity of this five-category ADNEX MR SCORING system was subsequently verified by independent study groups also confirming that it might lead to the standardization of MRI reporting for ovarian masses [43][44][45]. Very recently, the MRI working group for the Ovarian-Adnexal Imaging-Reporting and Data System (O-RADS) confirmed with a prospective multicenter study the performance of the ADNEX MR SCORING system (now called the O-RADS MRI score), that represents the current standard in the field [46].…”
Section: Gynecological Malignancies: Ovarian Masses and Endometrial Cmentioning
confidence: 96%
“…Our validity results of MRI are lower than results of Guerra et al (17) study in Portugal which revealed MRI sensitivity of 98%, specificity of 93%, +ve predictive value of 92%, -ve predictive value of 98% and accuracy of 95% in the diagnosis of malignant adnexal masses. In Brazil, Pereira et al (18) conducted a study on 237 women with adnexal masses using ADNEX MR scoring which showed that MRI sensitivity and specificity in the diagnosis of malignancy were 94.9% and 97.5%, respectively. The MRI is shown to have high sensitivity in diagnosing malignant adnexal mass approaching 96.6% while the specificity is between 83.7% -94.0% (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Комплексная МРТ позволяет отнести к доброкачественным ОЯ, которые по данным рутинной МРТ были ложно диагностированы как ЗОЯ, что является серьезной проблемой в клинике и приводит к выбору неадекватных стратегий и тактики лечения [29].…”
Section: таблица 2 изменение сигнала оя при комбинированном использовunclassified
“…На базе системы AMRSS было проведено проспективное исследование 200 пациенток (237 ОЯ) с упрощенным протоколом ДМРТКУ (с низким временным разрешением в 30, 60, 90, 120 и 150 с при высоком пространственном разрешении), в ходе которого два радиолога анализировали категории ADNEX MR по следующим пяти барьерным критериям [29]:…”
Section: Reviewsunclassified
See 1 more Smart Citation